PENGARUH EKSTRAK JAHE (Zingiber officinale) DAN LAMA PERENDAMAN TERHADAP KEKUATAN TRANSVERSAL RESIN AKRILIK KURING PANAS - , GITA RULIANTI, drg. Suparyono Saleh, Sp.Pros.(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Heat-cured acrylic resin is one of dental materials that can be used to manufacture the denture base. Acrylic resin denture base should have adequate strength and able to withstand the masticatory pressure. Transverse strength test represents the masticatory pressure applied to denture base. Ginger (Zingiber officinale) has many functions, one of which is as the main ingredient of traditional beverage consumed by many Indonesians like ginger tea or wedang ronde. The purpose of this study was to investigate the effect of ginger (Zingiber officinale) extract and immersion time on the transverse strength of heat-cured acrylic resin denture base. Heat-cured acrylic resin plate sized 65x10x2.5 mm was immersed in 10% concentration of ginger extract and aquadest as control for 1 hour and 3 hours. The transverse strength was measured using Universal Testing Machine and the span of two supporting parts was 50 mm. The data was analyzed using two-way anova. The result showed no significant difference in transverse strength of heat-cured acrylic resin between groups immersed in 10% ginger extract with control groups (p>0.05). There was a significant difference between the group of acrylic resin immersed for 1 hour and the group of acrylic resin immersed for 3 hours, either on 10% ginger extract or aquadest (p<0.05). Conclusion of this study was ginger extract statistically cannot decreased the transverse strength of heat-cured acrylic resin. Immersion time decreased the transverse strength of heat-cured acrylic resin due to water sorption.